Cosmeceutical properties of p-hydroxybenzoic acid and use of microencapsulation technique to ensure controlled release - Taofiq, Oludemi (2019)
Topical formulations are designed to exert multifunctional benefits to the skin, and the interest on natural bioactive compounds as cosmeceutical ingredients have recently received increased attention [1]. However, the utilization of natural ingredients can present constraints related to their stability (e.g. against pH and temperature), being microencapsulation a useful strategy to overcome some of these limitations [2]. The present work describes p-hydroxybenzoic acids anti-inflammatory, anti-tyrosinase, and antimicrobial activity. The compound was further microencapsulated using the atomization/coagulation method, with sodium alginate coagulated with calcium chloride. The obtained microspheres were characterized in terms of morphology, particle size distribution, and encapsulation efficiency. Free and microencapsulated forms were then incorporated into a semisolid cosmetic base formulation and HPLC-DAD was used to screen the presence of the compound in the final formulation. p-Hydroxybenzoic acid showed anti-inflammatory (EC50 = 195 ± 9 μg/mL), anti-tyrosinase (EC50 = 1.86 ± 0.01 mg/mL), and antimicrobial activity against a panel of Gram positive and Gram negative bacteria, and also Candida albicans. The microparticles showed spherical morphology, with various sizes (D10, D50 and D90 representing 20.5, 74.6, and 206 μm, respectively), little agglomeration, and a unimodal and bimodal particle size distribution (number and volume, respectively). Encapsulation efficiency and yield were 88.3% and 57.8%, respectively. After incorporation, the formulation containing free forms of the compound maintained some of its bioactive properties, while the encapsulated forms preserved the bioactivity showing a slow release profile of the compounds. In conclusion, the studied compound showed interesting bioactive properties and can be used in the development of multifunctional cosmeceutical formulation. The adopted encapsulation strategy also provides a suitable alternative to prolong retention of bioactive compounds for subsequent release (sustained release), thereby preserving its bioactivity over time.